The SAGE handbook of social media research methods - Sloan, Luke; Quan-Haase, Anabel (Los Angeles London SAGE reference, 2017)
With coverage of the entire research process in social media, data collection and analysis on specific platforms, and innovative developments in the field, this handbook is the ultimate resource for those looking to tackle the challenges that come with doing research in this sphere.
"The SAGE Handbook of Social Media Research Methods offers a step-by-step guide to overcoming the challenges inherent in research projects that deal with 'big and broad data,' from the formulation of research questions to the interpretation of findings. The Handbook includes chapters on specific social media platforms such as Twitter, Sina Weibo and Instragram, as well as a series of critical chapters" -- Back cover.
1. Introduction to the Handbook of social media research methods : goals, challenges and innovations / Anabel Quan-Haase and Luke Sloan -- Part I. Conceptualising & designing social media research. 2. What is social media and what questions can social media research help us answer? / Lori McCay-Peet and Anabel Quan-Haase -- 3. Big data -- hype or revolution? / Rob Kitchin -- 4. Building interdisciplinary social media research teams : motivations, challenges, and policy frameworks / Anabel Quan-Haase and Lori McCay-Peet -- 5. Social media users' views on the ethics of social media research / Kelsey Beninger -- 6. The role of online reputation management, trolling, and personality traits in the crafting of the virtual self on social media / Shuzhe Yang, Anabel Quan-Haase, Andrew D. Nevin and Yimin Chen -- 7. Social science 'lite'? : deriving demographic proxies from Twitter / Luke Sloan -- Part II. Collection & storage. 8. Think before you collect : setting up a data collection approach for social media studies / Philipp Mayr and Katrin Weller -- 9. Overview -- the social media data processing pipeline / David M. Brown, Adriana Soto-Corominas, Juan Luis Suárez and Javier de la Rosa -- 10. The role of APIs in data sampling from social media / Dietmar Janetzko -- 11. Data storage, curation and preservation / Alex Voss, Ilia Lvov and Sara Day Thomson -- 12. Using social media in data collection : designing studies with the qualitative e-research framework / Janet Salmons -- Part III. Qualitative approaches to social media data. 13. Small data, thick data : thickening strategies for trace-based social media research / Guillaume Latzko-Toth, Claudine Bonneau and Mélanie Millette -- 14. Visuality in social media : researching images, circulations and practices / Martin Hand -- 15. Coding of non-text data / Diane Rasmussen Pennington -- 16. Twitter as method : using Twitter as a tool to conduct research / Bonnie Stewart -- 17. Small stories research : a narrative paradigm for the analysis of social media / Alexandra Georgakopoulou -- Part IV. Quantitative approaches to social media data. 18. Geospatial analysis / Olga Buchel and Diane Rasmussen Pennington -- 19. Pragmatics of network centrality / Shadi Ghajar-Khosravi and Mark Chignell -- 20. Predictive analytics with social media data / Niels Buus Lassen, Lisbeth la Cour and Ravi Vatrapu -- 21. Deception detection and rumor debunking for social media / Victoria L. Rubin -- Part V. Diverse approaches to social media data. 22. From site-specificity to hyper-locality : performances of place in social media / Nadav Hochman -- 23. Analyzing social media data and other data sources : a methodological overview / Frauke Zeller -- 24. Listening to social rhythms : exploring logged interactional data through sonification / Jack Jamieson and Jeffrey Boase -- 25. Innovative social location-aware services for mobile phones / Bernhard Klein and Ulf-Dietrich Reips -- Part VI. Research and analytical tools. 26. COSMOS : the collaborative on-line social media observatory / Jeffrey Morgan -- 27. Social Lab : an 'open source Facebook' / Ulf-Dietrich Reips and Pablo Garaizar -- 28. R for social media analysis / Simon Hegelich -- 29. GATE : an open-source NLP toolkit for mining social media / Kalina Bontcheva -- 30. A how-to for using Netlytic to collect and analyze social media data : a case study of the use of Twitter during the 2014 Euromaidan Revolution in Ukraine / Anatoliy Gruzd, Philip Mai and Andrea Kampen -- 31. Theme detection in social media / Daniel Angus -- 32. Sentiment analysis / Mike Thelwall -- Part VII. Social media platforms. 33. The ontology of tweets : mixed-method approaches to the study of Twitter / Dhiraj Murthy -- 34. Instagram / Linnea Laestadius -- 35. Weibo / Xiao Hu, Chen Qiao and King-wa Fu -- 36. Foursquare / Matthew J. Williams and Martin Chorley -- 37. Facebook as a research tool in the social and computer sciences / Jessica Vitak -- 38. Big Data and political science : the case of VKontakte and the 2014 Euromaidan Revolution in Ukraine / Anatoliy Gruzd and Ben O'Bright -- 39. A retrospective on state of the art social media research methods : ethical decisions, big-small data rivalries and the spectre of the 6Vs / Luke Sloan and Anabel Quan-Haase -- Index.
"SAGE reference."
Includes bibliographical references and index.
Also issued electronically.
Keywords: Social media -- Research; Social media -- Research -- Methodology; Social media -- Research -- Handbooks, manual, etc; Data mining